Determinants of Non-Participation in Population-Based Breast Cancer Screening: A Systematic Review and Meta-Analysis - Ding, Lilu; Wang, J.; Greuter, M. J. W.; Goossens, M.; Van Hal, Guido; de Bock, Geertruida H. (Frontiers in Oncology, 2022)
Background Breast cancer (BC) screening can be performed in a screening program (BCSP) or in opportunistic screening. The existing reviews on the determinants of non-participation depend on self-reported data which may be biased. Furthermore, no distinction was made between the probably different determinants of both screening strategies. Objective To find the determinants of non-participation in BCSP by means of a meta-analysis. Methods PubMed, Embase, and Web of Science were searched for observational studies which quantified factors associated with non-participation in BCSP in a general population. Studies on opportunistic screening, and studies using self-reported data were excluded. A random-effect model was used to calculate pooled odds ratios (ORs) and 95% confidence intervals (CIs). Potential sources of heterogeneity were explored by stratification of the results. Results Twenty-nine studies with in total 20,361,756 women were included. Low income (OR: 1.20, 95%CI: 1.10-1.30), low education (OR: 1.18, 95%CI: 1.05-1.32), living far from an assigned screening unit (OR: 1.15, 95%CI: 1.07-1.24), being immigrant (OR: 2.64, 95%CI: 2.48-2.82), and having a male family doctor (OR: 1.43, 95%CI: 1.20-1.61) was associated with higher non-participation in screening Reminders sent to non-attenders and estimations of ORs (adjusted or not) partly explained substantial heterogeneity. Conclusion In this meta-analysis excluding studies on the non-participation in opportunistic screening, or with self-reported data on non-participation, the well-known determinants for non-participation are still significant, but less strong. This analysis supports the relevance of meta-analysis including only studies with registered non-participation in a BCSP.